Transformation of the halal food industry in Bali Province: Evaluation of the effectiveness of halal labeling systems on local economic growth‎ - Hidayati, Amalia Nuril; Syaichoni, Ahmad (Journal of Islamic Economics Lariba, 2025)
IntroductionHalal tourism has become a strategic priority in Indonesia, positioning the country as a global leader in the halal economy. Bali, a Hindu-majority region with unique cultural identity, faces the dual challenge of accommodating rising demand for halal-certified products from Muslim tourists while preserving local traditions. The effectiveness of halal labeling in this context is not only a matter of consumer assurance but also of industry transformation and economic development.ObjectivesThis study aims to analyze the effectiveness of the halal labeling system in driving the transformation of the halal food industry in Bali. It examines the role of halal labeling in product innovation, process improvement, marketing expansion, and institutional strengthening, and assesses its broader contribution to regional economic growth.MethodThe research uses a qualitative document analysis approach, synthesizing laws, policy frameworks, certification data, statistical records, and comparative international experiences. The analysis applies an endogenous growth perspective to evaluate how halal labeling functions as a catalyst for innovation, industry upgrading, and competitiveness in Bali’s halal food sector.ResultsThe findings reveal that halal labeling encourages significant transformation. Products are reformulated to meet halal requirements without diminishing cultural authenticity. Processes are upgraded through assurance systems, training, and quality management. Marketing strategies expand into Muslim-friendly branding and digital promotion, increasing access to international markets. Institutions are strengthened through the establishment of halal centers and multi-stakeholder collaboration. Data indicate that the number of halal-certified businesses in Bali increased nearly twentyfold between 2020 and 2024, though only about ten percent of micro, small, and medium enterprises are certified. The contribution of Muslim tourists to Bali’s tourism revenue also grew substantially during this period.ImplicationsThe study demonstrates that halal labeling operates as an effective instrument of structural change in a non-Muslim context when implemented with cultural sensitivity, institutional support, and facilitation for small enterprises. By fostering product upgrading, market diversification, and tourism competitiveness, halal labeling contributes to Bali’s economic recovery and sustainable growth.Originality/NoveltyThis study extends the discourse on halal labeling by reframing it from a narrow assurance mechanism into a driver of structural transformation. It integrates Islamic ethical foundations, international comparative experiences, and endogenous growth theory to propose a context-sensitive model for implementing halal labeling in minority-Muslim destinations.